Faktor-Faktor Yang Mempengaruhi Muzakki Dalam Membayar Zakat Perniagaan (Studi Terhadap Pedagang Di Kota Banda Aceh) - Ratna Yunita; Muhammad Zulhilmi; Rina Desiana (Jurnal Ilmiah Mahasiswa Ekonomi dan Bisnis Islam, 2021)
Commercial zakat is zakat issued on property ownership intended for buying and selling, which of course has reached the nishab or haul. Trading activities are efforts made by humans to obtain halal sustenance aimed at being able to meet the needs of human life. This study was conducted to determine the factors that influence muzakki in paying commercial zakat (study of traders in Banda Aceh City). This research is a field research (Field Research) using quantitative methods. Sampling method using Non-Probability Sampling technique. The sample used in this study was 100 muzakki or traders in Banda Aceh City. The data used in this study is primary data which is data obtained directly from respondents by distributing questionnaires. The results of the multiple regression analysis show that partially trust and self-awareness factors have a positive and significant effect on muzakki in paying commercial zakat (study pf traders in Banda Aceh City). On the other hand partially understanding factors do not have a significant effect on muzakki in paying zakat on brokerage (study of traders in Banda Aceh City)